2018
DOI: 10.1242/dev.161893
|View full text |Cite
|
Sign up to set email alerts
|

Forced lipophagy reveals that lipid droplets are required for early embryonic development in mouse

Abstract: Although autophagy is classically viewed as a non-selective degradation system, recent studies have revealed that various forms of selective autophagy also play crucial physiological roles. However, the induction of selective autophagy is not well understood. In this study, we established a forced selective autophagy system using a fusion of an autophagy adaptor and a substrate-binding protein. In both mammalian cells and fertilized mouse embryos, efficient forced lipophagy was induced by expression of a fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…Moreover, autophagy in the central nervous system activates lipophagy and lipolysis in peripheral tissues as a response to cold exposure [ 256 ]. The induction of forced lipophagy in mouse embryos reduces lipid droplet levels during development and results in retardation, suggesting a novel role of lipid droplets and lipophagy during embryogenesis [ 257 ]. A sudden depletion of glucose in yeast cells activates AMPK-dependent lipid droplet breakdown by microautophagy, i.e., microlipophagy, and provides energy for long-term survival [ 258 ].…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
“…Moreover, autophagy in the central nervous system activates lipophagy and lipolysis in peripheral tissues as a response to cold exposure [ 256 ]. The induction of forced lipophagy in mouse embryos reduces lipid droplet levels during development and results in retardation, suggesting a novel role of lipid droplets and lipophagy during embryogenesis [ 257 ]. A sudden depletion of glucose in yeast cells activates AMPK-dependent lipid droplet breakdown by microautophagy, i.e., microlipophagy, and provides energy for long-term survival [ 258 ].…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
“…The LC3-interacting protein SQSTM1/p62 is a key autophagic protein for cell homeostasis mediating the selective specific degradation of protein aggregates and cytoplasmic bodies (Lin et al 2013). Recent studies have described SQSTM1/p62 as a key mediator in lipolysis (Lee et al 2010) and also, in lipophagy (Tatsumi et al 2018;Wang et al 2017). SQSTM1/p62 protein (Fig.…”
Section: Lipophagymentioning
confidence: 99%
“…Lipophagy was first discovered in liver and, currently, is described in many other tissues (Singh and Cuervo 2012). SQSTM1/p62 participates in the selective removal of organelles, as mitochondria or LDs through autophagy (Tatsumi et al 2018;Wang et al 2017). SQSTM1/p62 and other autophagic machinery directly contributes to the mobilization of lipids from LDs to lysosomes, where they get degraded by lipases (Singh and Cuervo 2012).…”
Section: Discusionmentioning
confidence: 99%
“…As discussed above, function of lipophagy as a second lipolytic pathway in mammals is now widely accepted (Singh et al 2009;Liu et al 2016;Dupont et al 2014;Haemmerle et al 2006;Lizaso et al 2013;Tatsumi et al 2018;Cingolani & Czaja 2016;Sztalryd & Brasaemle 2017). With most autophagy-related proteins being closely conserved in C. elegans (Chen et al 2017), it is evolutionarily very likely that lipophagy would be conserved and act as an alternative lipolytic pathway in C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…While cold exposure is a simple, robust and consistent way to indirectly study certain aspects of lipolysis, direct studies of such animals are difficult in regard to cold-induced malformations and embryo accumulation (Liu et al 2017). Activated lipolysis is important in embryonic development in a variety of organisms, from Drosophila to several species of mammals (Teixeira et al 2003;Sastre et al 2014;Xu et al 2018;Tatsumi et al 2018), promising to offer an interesting model for direct studies. Consistently, we have previously shown that in C. elegans, early embryos display distorted perinuclear hyperaccumulation of lipids, but eventually, sufficient lipolysis is accomplished and animals overcome this lack of PLIN by possibly a different mechanism, proposing it could be autophagy (Chughtai et al 2015).…”
Section: Depletion Of Plin-1 Dramatically Increases Autophagic Activimentioning
confidence: 99%